The Philosophical Significance of Alisher Navoiy’s Ideas In Educating Society and Shaping The Perfect Human Being - Uzakova Lola Abdurashitovna (Indonesian Journal Publisher, 2025)
The importance of Alisher Navoiy’s spiritual heritage in the evolution of society is examined in this article, along with his philosophical beliefs from a scientific standpoint. The study of Navoiy’s philosophical and creative legacy is currently receiving particular attention in international academia. The poet’s philosophical and ethical stances, as well as the humanistic quality of his artistic creations, are being thoroughly examined by academics at esteemed universities and research facilities across the globe. The essay investigates the ways in which the great thinker’s writings tackle the concepts of justice, moral excellence, patriotism, and perfection. It also talks about his social justice beliefs and his function in state governance. The study also looks at the potential for incorporating Navoiy’s teachings into the training and education process as well as the influence of his heritage on the moral upbringing of the next generation. In order to emphasise Navoiy’s works’ applicability in the modern world, the article discusses their literary, philosophical, and historical facets